Effect of Socio-Cultural Environment in Business Organizations - Adhikari, Pradeep (Ganeshman Darpan, 2026)
Socio-cultural environment includes values, beliefs, customs, traditions, religion, education, lifestyle, and demographic characteristics that shape the behavior of individuals and organizations. The main objective of this study examines the effect of socio-cultural factors in business activities and consumer behavior on Nepalese society. The study explores these major factors: the role of socio-cultural environment in business growth and sustainability, consumer behavior, changing lifestyle and family structure, education and literacy level, religious beliefs, effects of family structure and urbanization, and changing consumer lifestyle as well as opportunity and threat. Findings indicate that socio-cultural factors significantly affect demand on market, consumption patterns, organizational culture, and operational activities. The practice of festivals, traditions, and religious system it creates seasonal demand, while rising education and literacy levels it creates synergetic power for consumer awareness and acceptance for quality and ethical products. Similarly, changing family system joint to nuclear and rapid urbanization has increased demand for modern, facility based and technology-based high-quality goods and services. The study also highlights that changing lifestyles such as new markets and innovation create opportunities and increased competition and uncertainty and resistance to change with external changes create threats. In this study we conclude that socio-cultural environment plays a crucial role in base for business success and sustainability. Businesses that understand sociocultural changes can better identify opportunities, reduce risks, and achieve long-term competitiveness with strategic fit in the Nepalese dynamic market era.